Immunohistochemistry and Polymerase Chain Reaction for Detection Human Papilloma Virus in Warts: A Comparative Study - Lee, Hong Sun (Ann Dermatol, 2016)
BACKGROUND: Immunohistochemistry and polymerase chain reaction (PCR) are the most widely used methods for the detection of viruses. PCR is known to be a more sensitive and specific method than the immunohistochemical method at this time, but PCR has the disadvantages of high cost and skilled work to use widely. With the progress of technology, the immunohistochemical methods used in these days has come to be highly sensitive and actively used in the diagnostic fields. OBJECTIVE: To evaluate and compare the usefulness of immunohistochemistry and PCR for detection human papilloma virus (HPV) in wart lesions. METHODS: Nine biopsy samples of verruca vulgaris and 10 of condyloma accuminatum were examined. Immunohistochemical staining using monoclonal antibody to HPV L1 capsid protein and PCR were done for the samples. DNA sequencing of the PCR products and HPV genotyping were also done. RESULTS: HPV detection rate was 78.9% (88.9% in verruca vulgaris, 70.0% in condyloma accuminatum) on immunohistochemistry and 100.0% for PCR. HPV-6 genotype showed a lower positivity rate on immunohistochemistry (50.0%) as compared to that of the other HPV genotypes. CONCLUSION: Immunohistochemistry for HPV L1 capsid protein showed comparable sensitivity for detection HPV. Considering the high cost and great effort needed for the PCR methods, we can use immunohistochemistry for HPV L1 capsid protein with the advantage of lower cost and simple methods for HPV detection.